Acoustic characteristics of the island-endemic Parapelophryne scalpta (Anura: Bufonidae) from Hainan Island, China - Yeung, Ho Yuen; Yang, Jian-Huan (Zootaxa, 2020)
The Hainan Pygmy Toad Parapelophryne scalpta (Liu & Hu) is the single species of the genus Parapelophryne Fei, Ye & Jiang in the Family Bufonidae (Frost 2020) and is endemic to China’s Hainan Island, which lies within the tropics at 18°09′–20°10′N, 108°37′–111°03′E, with a land area of ca. 33,900 km2. The taxonomy status of this species has obtained much debates since its discovery: it was originally described by Liu et al. (1973) as a member of the genus Nectophryne Buchholz & Peters then allocated to Pelophryne Barbour by Ye & Fei (1978). On the basis of its unique morphological characters, Fei et al. (2003) erected a new genus Parapelophryne to discriminate P. scalpta from other bufonids. Some researchers, however, still listed the species under the genus Pelophryne (Stuart et al. 2008; Shi et al. 2011). Recently, the validity of the genus Parapelophryne is further confirmed by Matsui et al. (2015) on the basis of molecular analyses. Interestingly enough, Matsui et al. (2015)’s result showed that this extremely small-sized toad is a sister taxon of the large-sized toads of the genus Bufo Garsault, which is mainly distributed in temperate and subtropical regions of Eurasia (Frost 2020). Parapelophryne scalpta is a forest-dependent species and only inhabits in well-preserved evergreen broadleaf forests (Fei & Ye 2016). It is the smallest toad species in China with snout-vent length of 19–23 mm in adult males and 24–27 mm in females (Fei & Ye 2016). Due to their small size and elusive habits, little is known about the natural history of P. scalpta and its acoustic characteristics are still undocumented (Fei & Ye 2016). During a herpetological survey in Hainan in 2015, we luckily detected male calls of P. scalpta and obtained a short but clear record of the advertisement call of the species. Herein, we describe the acoustic characteristics and calling behavior of Parapelophryne scalpta.